2019
DOI: 10.21608/epsj.2019.46948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Probiotic Supplementation During Rearing Period on Subsequent Laying Performance of Local Laying Hens

Abstract: This study aimed to investigate the effect of dietary probiotic supplementation during rearing period on subsequent laying performance and physiological response of Sinai hens during laying period. A total number of 360 Sinai chicks, one old day were used in the current trail. Chicks were divided into 4 equal groups each of 3 replicates. Experimental groups were as follows, 1 st group served as a control and fed the basal experimental diets, while, the 2 nd , 3 rd and 4 th groups were fed the basal diets suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Layer diets have considerable high ash content due to the high requirement for calcium which is provided through inclusion of limestone in the rations. The calcium and phosphorus content were within the range of 3.0 -4.20% and 0.40-0.64% respectively, reported by (Rizk et al, 2019;Yan et al, 2019). Ca and P are the key macro minerals that play a critical role in bone development, mineralization and eggshell formation with the former 94% and latter 1% in eggshell (Aditya et al, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…Layer diets have considerable high ash content due to the high requirement for calcium which is provided through inclusion of limestone in the rations. The calcium and phosphorus content were within the range of 3.0 -4.20% and 0.40-0.64% respectively, reported by (Rizk et al, 2019;Yan et al, 2019). Ca and P are the key macro minerals that play a critical role in bone development, mineralization and eggshell formation with the former 94% and latter 1% in eggshell (Aditya et al, 2021).…”
Section: Discussionmentioning
confidence: 76%
“…The reverse picture denoted by Belhassen et al (2016) who stated that viability rate of kits at birth in the first parity during the first 21 days was significantly (P<0.05) better in supplemented group, while such difference was not observed during the second parity. On the other hand, on chicks Rizk et al (2019) noticed that total embryonic mortality (%) did not significantly changed between probiotic dietary treatments groups and the control one. On line with the obtained MR% the findings of Bovera et al (2010) who reported that mannan oligosaccharides (MOS) at the rate of 1.0 g/kg in the diets of rabbits could reduce rabbit mortality, since they recorded the highest (P<0.05) total mortality rate for rabbits fed antibiotics than for those fed 0.5, 1.0 and 1.5 g MOS/Kg diet (34.2% Vs. 17.7, 7.75 and 17.1%).…”
Section: Productive and Reproductive Traits Of Doesmentioning
confidence: 84%
“…Moreover, Mostafa et al (2014) using probiotics (AVI-BAC and BGY) postpartum on cows and Nde et al (2014) with Celmanax® (yeast culture product) addition to diets of sheep. Rizk et al (2019) observed that feed consumption significantly increased for chicks fed diet supplemented with 0.3 and 0.5 g probiotic/kg than the control group at the whole period (1-20 wks. of age).…”
Section: Productive and Reproductive Traits Of Doesmentioning
confidence: 86%
See 1 more Smart Citation
“…Also, one reason for the observed improvement in egg hatchability of probiotic fed group could be due to improved haugh unit (Tona et al 2002). Rizk et al (2019) showed that addition of 0.3 and 0.5 g commercial probiotics (contains LAB (Lactobacillus lactis) 2.5 × 10 8 CFU, Bacillus subtilis 1.8 × 10 9 CFU/ g product) were significantly increased fertility and hatchability during rearing period as compared to the control diet. Darsi and Zhaghari (2021) showed that dietary supplementation of Lactobacillus sporogenes as probiotic in White Leghorn layer breeders diet significantly increased egg hatchability P ≤ 0.05).…”
Section: Resultsmentioning
confidence: 99%